Eucaristia: pluralidade de dimensões na unidade do mistério - Tavares, Sinivaldo Silva (Revista Eclesiástica Brasileira, 2003)
Frei Sinivaldo, Professor no Instituto Teológico Franciscano (ITF) de Petrópolis, RJ, reflete neste artigo sobre a inesgotável riqueza da Eucaristia, mysterium fidei por antonomásia. Em traços firmes e claros, expõe distintas facetas da Eucaristia, com ênfase especial nas dimensões “testamento” (“corpo entregue” e “sangue derramado”) e “memorial” (“anámnesis”) do Senhor. Num segundo momento, aborda as dimensões epiclética, escatológica, ético-social e cósmica da Eucaristia. Encerrando a reflexão, à luz do princípio “lex orandi, lex credendi”, convida os teólogos sistemáticos a enveredar pela via mistagógica, antes de arriscar-se no intrincado labirinto da teoria escolástica da transubstanciação. Abstract: In this article, Fray Sinivaldo, a Professor at the Franciscan Theological Institute (ITF) in Petrópolis, RJ, reflects upon the inexhaustible wealth of the Eucharist, mysterium fidei by antonomasia. In strong and clear strokes, he exposes different facets of the Eucharist, giving special emphasis to its dimensions “testament” (“surrendered body” and “shed blood”) and “memorial” (anamnesis) of the Lord. In a second moment, he deals with the epicletical, eschatological, ethico-social and cosmic dimensions of the Eucharist. Ending the reflection, in the light of the principle “lex orandi, lex credendi” he invites all systematic theologians to make their way toward the mystagogical road, before risking themselves in the complex labyrinth of the scholastic theory of transubstantiation.